Estimating Intellectual Capital and its Impact on Firms’ Performance : Use of A-VAIC and M-VAIC Models - Gupta, Kanishka; Gaur, Dolly; Bhatia, Prakash (Indian Journal of Finance, 2023)
The study examined the contribution of intellectual capital to companies’ overall performance. Also, a comparison between the effectiveness of the adjusted value-added intellectual coefficient (A-VAIC) and the modified value-added intellectual coefficient (M-VAIC) model for estimating IC components and analyzing their impact on firms’ performance was attempted. The study was carried out for 405 Indian companies listed on the NSE-500 index for 10 years (20102011 to 20192020). It was found in the results that intellectual capital is indeed helpful in improving firms financial and market performance. However, the M-VAIC is more detailed and precise. Hence, the IC components estimated using it can explain companies’ performance more effectively than the A-VAIC.